Study on neutronics of VVER-1200 with accident tolerant fuel cladding. (February 2019) - Fejt, F.; Sevecek, M.; Frybort, J.; Novak, O.
Highlights: ZrSi2 coating reaches the smallest multiplication factor penalty. Cr and CrN coatings reach the largets multiplication factor penalty. All coatings shift neutron spectrum to higher energy. Coatings have minimal effects on feedback coefficients. Higher energy spectrum may lead to higher Pu production. Abstract: Protective coatings deposited on traditional Zr-based fuel cladding materials potentially enhance accidental tolerance of Light Water Reactors due to reduced interaction between water and Zr alloys during accidental conditions. Enhancement of cladding performance and reduction of negative effects, such as heat generation, hydrogen production, oxidation, and embrittlement can be achieved by deposition of various coatings that are widely studied around the world. Even though thermal, mechanical, and chemical responses during accidental conditions are the main concern for these materials, the actual application of coated materials will be linked to standard operating conditions including economic consequences and transient response. Reference VVER-1200 fuel system with five coatings (Cr, CrN, ZrSi2, Cr2 AlC, Fe(Cr)(Al)) is investigated from the neutron-physical point of view using the calculation package SCALE 6.2.2. In addition to the multiplication factor, specific fuel safety criteria are also examined for both the fresh fuel assemblies and fuel assemblies with burn-up up-to 70 MWd/ t HM . All studied coatings entail certain negative effects in comparison with the reference case. The closest behavior to the reference VVER-1200 fuel assembly is found for ZrSi2 coating followed by Cr2 AlC and Fe(Cr)(Al) coatings. Both Cr and CrN materials exhibit significant differences compared to the reference case.